Pathological and behavioral risk factors for higher serum c-reactive protein concentrations in free-living adults - A Brazilian community-based study - Moreto, Fernando [UNESP]; De Oliveira, Erick Prado [UNESP]; Manda, Rodrigo Minoru [UNESP]; Torezan, Gabriel Augusto [UNESP]; Teixeira, Okesley [UNESP]; Michelin, Edilaine [UNESP]; Burini, Roberto Carlos [UNESP] (Springer Nature, 2013)
Low-grade chronic systemic inflammation is often associated with chronic non-communicable diseases, and its most frequently used marker, the C-reactive protein (CRP), has become an identifier of such diseases as well as an independent predictor for cardiovascular disorders and mortality. CRP is produced in response to pro-inflammatory signaling and to individual and behavioral factors, leading to pathological states. The aim of this study was to rank the predicting factors of high CRP concentrations in free-living adults from a community-based sample. We evaluated 522 adults (40-84 years old; 381 women) for anthropometric characteristics, dietary intake, clinical and physical tests, and blood analysis. Subjects were assigned to groups, according to CRP concentrations, as normal CRP (G1;<3.0 mg/L; n = 269), high CRP (G2; 3.0-6.0 mg/L; n = 139), and very high CRP (G3; >6.0 mg/dL; n = 116). Statistical comparison between groups used one-way ANOVA or Kruskal-Wallis tests, and prediction of altered values in increasing CRP was evaluated by proportional hazard models (odds ratio). CRP distribution was influenced by gender, body mass index, body and abdominal fatness, blood leukocytes, and neutrophil counts. The higher CRP group was discriminated by the above variables in addition to lower VO2max, serum metabolic syndrome components (triglycerides, glucose, and HDL cholesterol), higher insulin, homeostasis assessment of insulin resistance, uric acid, gamma-GT, and homocysteine. After adjustments, only fatness, blood leukocytes, and hyperglycemia remained as independent predictors for increased serum CRP concentrations. Intervention procedures to treat low-grade chronic inflammation in overweight women would mainly focus on restoring muscle mass and functions in addition to an antioxidant-rich diet. © 2012 Springer Science+Business Media, LLC.
Keywords: hyperglycemia; inflammation; metabolic syndrome; predictors; C reactive protein; gamma glutamyltransferase; glucose; high density lipoprotein cholesterol; homocysteine; insulin; triacylglycerol; uric acid; adult; aged; anthropometry; blood analysis; body fat; body mass; Brazil; clinical examination; community; controlled study; cross-sectional study; dietary intake; female; fitness; health behavior; homeostasis; human; insulin resistance; leukocyte count; major clinical study; male; metabolic syndrome X; neutrophil count; nutritional assessment; oxygen consumption; physical examination; prediction; protein blood level; risk factor; Abdominal Fat; Adult; Aged; Aged, 80 and over; Anthropometry; Blood Glucose; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cross-Sectional Studies; Female; Food Habits; Homocysteine; Humans; Hyperglycemia; Inflammation; Insulin; Insulin Resistance; Leukocyte Count; Male; Metabolic Syndrome X; Middle Aged; Neutrophils; Nutrition Assessment; Obesity; Proportional Hazards Models; Risk Factors; Triglycerides; Uric Acid